30GT Fishing Vessel Electrical System Design - M. Basuki Rahmat; Joessianto Eko P; Annas Singgih S; Rona R; Hendro Agus W; Purwidi Asri (LPPM of NAROTAMA UNIVERSITY, 2022)
The ship electrification process is the process of installing or providing electric power to supply all the electrical power needs for ships. In general, main electricity supply will be provided, and emergency supplies in the form of batteries or emergency generators that are able to survive supplying emergency loads such as navigation equipment, navigation lights, and emergency lighting for about 3 hours. Another consideration in the electrification process on fishing vessels is also aimed at reducing dependence or even replacing conventional fuel. Of course, not all machines or equipment that are usually operated with conventional fuel can be directly replaced with electrical energy. The implementation of electrification on fishing boats takes into account the technological and cultural aspects of fishermen so that not all of them will be directly replaced by electrical energy.